State-business relations and improvement of corporate governance in Russia - Andrei Yakovlev (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
In this paper, we analyze the influence of the state on the improvement of corporate governance in Russia of the early 2000s. Taking into account the low quality of market institutions in the 1990s (i.e., the market failure phenomenon), we assume that state intervention as the "second best" institution had a positive impact in this case. Using a dataset of 822 joint-stock companies, we tested this hypothesis in two types of corporate models – state-owned or mixed firms and "politically connected" firms. The first model confirmed a strong positive influence of state ownership on the corporate governance in Russia in 2001-2004. The estimation results of this model are statistically robust in different specifications. We connect this result with attempts of the Russian government to use standard mechanisms and procedures of corporate governance to defend its property rights in its relations with state-owned and mixed enterprises.
URN:NBN:fi:bof-201408072193
Keywords: 330